Effects of muscle glycogen on performance of repeated sprints and mechanisms of fatigue - Smith Rockwell, J.; Walberg Rankin, J.; Dixon, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2003)
This study investigated the effect of initial muscle glycogen on performance of repeated sprints and some potential mechanisms for an effect of glycogen on fatigue. Eight subjects performed 2 cycling trials (repeated 60-s sprints) following consumption of either a high carbohydrate (HC) or a low carbohydrate (LC) diet. Muscle biopsies and blood samples were collected at baseline, following a 15% (15% fatigue) and a 30% decline in sprint performance (30% fatigue), when exercise was terminated. Baseline muscle glycogen levels [346 +/- 19 HC (SEM) vs. 222 +/- 19 mmol/kg dw LC] and total exercise time to 30% fatigue were higher following HC than LC (57.5 +/- 10.0 vs. 42.0 +/- 3.6 min; p <.05). Similar significant (p <.05) decreases over the entire exercise bout were seen in muscle glycogen (43%), creatine phosphate (CP; 35%), and sarcoplasmic reticulum (SR) Ca2+-uptake in isolated homogenized muscle (56%) for both trials (p >.05 between trials). The percentage decline in SR Ca2+-release was less for HC than LC (36% and 53%, respectively), but this was not statistically different. In summary, HC delayed fatigue during repeated sprints. As the reductions in muscle glycogen, CP, and SR function during exercise were not different by dietary treatment, these data do not support a link between whole muscle glycogen and SR function or CP reduction during repeated sprint exercise.